2015
DOI: 10.1016/j.chemosphere.2014.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoxetine on behavior, antioxidant enzyme systems, and multixenobiotic resistance in the Asian clam Corbicula fluminea

Abstract: h i g h l i g h t sGR, TR, ABCB1, ABCC1, and ABCG2 genes were identified in the clam. The siphoning behavior of the clam was inhibited by FLX. activity and malondialdehyde (MDA) content markedly increased (p < 0.05). Moreover, transcription of thioredoxin reductase (TR), glutathione peroxidase (GPx) and Glutathione S-transferase pi class (GSTpi) was significantly upregulated (p < 0.05), whereas glutathione reductase (GR) was markedly downregulated (p < 0.05). These findings suggest that FLX affects behavior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 49 publications
2
19
0
3
Order By: Relevance
“…On the contrary, others have found down-regulation of these genes (e.g. Chen et al, 2015;Gonzalez-Rey et al, 2014;Sun et al, 2014). These differences may be attributed to the particular conditions of each experiment, to the pollutant and to the tested species.…”
Section: Resultsmentioning
confidence: 81%
“…On the contrary, others have found down-regulation of these genes (e.g. Chen et al, 2015;Gonzalez-Rey et al, 2014;Sun et al, 2014). These differences may be attributed to the particular conditions of each experiment, to the pollutant and to the tested species.…”
Section: Resultsmentioning
confidence: 81%
“…On another hand, A. woodiana also adjust it's antioxidant ability by enhancing antioxidant enzyme expression to eliminate ROS. If generation of ROS are under a weak level, anti-oxidant enzyme expressions should be up-regulated that contribute to endure oxidative stresses [25,26,39,44]. Once the production of ROS is exceed the eliminating ability of cells that cause a shift between oxidants and antioxidants in favor of oxidants, and result in chronic inflammation, apoptosis In the PBDE-209 treated groups, up-regulations of AwSOD and AwCAT expression exhibited a time-and dose-dependent pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Orchestra of anti-oxidant enzymes is a key hallmark of organism homeostasis. Moderate oxidative stress in a shorter time may function as an important player to induce different anti-oxidant enzyme expressions to deal with different ROS [25,26,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same crab species, 120 μg/L of fluoxetine significantly altered locomotor behaviors (Mesquita, Guilhermino, & Guimaraes, 2011). Several other studies have demonstrated that fluoxetine leads to adverse physiological and behavioral outcomes in aquatic organisms that could alter their functional roles within the community (Bossus, Guler, Short, Morrison, & Ford, 2014; Chen, Zha, Yuan, & Wang, 2015; Dzieweczynski & Hebert, 2012; Munari, Marin, & Matozzo, 2014; Peters & Granek, 2016; Schultz et al., 2011). …”
Section: Introductionmentioning
confidence: 99%